Cost-effective opportunities for climate change mitigation in Indian agriculture - Sapkota, Tek Bahadur; Vetter, Sylvia H.; Jat, Mangi Lal; Sirohi, Smita; Shirsath, Paresh Bhaskar; Singh, Rajbir; Jat, Hanuman Sahay; Smith, Pete; Hillier, Jon; Stirling, Clare M. (Elsevier, 2019)
Long-term changes in average temperatures, precipitation, and climate variability threaten agricultural production, food security, and the livelihoods of farming communities globally. Whilst adaptation to climate change is necessary to ensure food security and protect livelihoods of poor farmers, mitigation of greenhouse gas (GHG) emissions can lessen the extent of climate change and future needs for adaptation. Many agricultural practices can potentially mitigate GHG emissions without compromising food production. India is the third largest GHG emitter in the world where agriculture is responsible for 18% of total national emissions. India has identified agriculture as one of the priority sectors for GHG emission reduction in its Nationally Determined Contributions (NDCs). Identification of emission hotspots and cost-effective mitigation options in agriculture can inform the prioritisation of efforts to reduce emissions without compromising food and nutrition security.